Theabrownins Produced via Chemical Oxidation of Tea Polyphenols Inhibit Human Lung Cancer Cells in vivo and in vitro by Suppressing the PI3K/AKT/mTOR Pathway Activation and Promoting Autophagy - Wang, Yongyong; Yuan, Yao; Wang, Chunpeng; Wang, Bingjie; Zou, Wenbin; Zhang, Ni; Chen, Xiaoqiang (Frontiers in Nutrition, 2022)
In the fermentation processing of dark tea, theabrownins (TBs) and carbohydrates and other substances are irreversibly complexed. The existing research on its biological activity is not based on free TBs. In this study, some brown polyphenol oxidized polymers, the generalized theabrownins (TBs-C), were prepared by alkali oxidation from tea polyphenols (TP). The inhibitory mechanism of TBs-C on non-small cell lung cancer (NSCLC) were studied. TBs-C had a stronger inhibition than TP on the NSCLC cell lines A549, H2030, HCC827, H1975, and PC9. Afterwards, A549 and H2030 cell lines were selected as subjects to explore the mechanism. TBs-C can inhibit proliferation, promote apoptosis, and cause G1 cell cycle arrest in the cells. Additionally, TBs-C also increased autophagic flux that promoted the death of lung cancer cells. TBs-C suppresses the PI3K/AKT/mTOR pathway activation, promotes autophagy, and increases the expression of p21 downstream of AKT, resulting in G1 cell cycle arrest. In xenotransplanted NSCLC nude mice derived from A549 cells, TBs-C significantly suppressed tumor growth by inhibiting the PI3K/AKT/mTOR pathway without causing hepatotoxicity, brain toxicity or nephrotoxicity. These findings will help advance the research and industrialization of theabrownins.